Fu’s subcutaneous needling facilitates muscle repair by regulating mitochondrial homeostasis in rat with chronic peripheral nervous pain - Chiu, Po-En; Fu, Zhonghua; Pan, Hung-Chuan; Tsai, Yi-Ching; Tsai, Chia-Yun; Hsu, Wei-Jen; Chou, Li-Wei; Lai, De-Wei (Frontiers in Physiology, 2025)
Sciatica, often resulting from lumbar disc herniation or nerve compression, disrupts electrical signal transmission, leading to muscle atrophy, mitochondrial dysfunction, and impaired energy metabolism. This study explored the therapeutic effects of Fu’s subcutaneous needling (FSN) in a chronic constriction injury (CCI) rat model, assessing its impact on neuropathic pain, muscle mass, and structural integrity. Histological and ultrastructural analyses demonstrated that FSN alleviated hypersensitivity, reduced muscle atrophy, preserved mitochondrial density, and maintained glycogen storage. Gene expression and pathway enrichment analyses revealed FSN’s involvement in PI3K–Akt, MAPK signaling, oxidative phosphorylation, and mitophagy, suggesting its role in modulating energy metabolism and cellular repair. FSN also normalized energy-related proteins FGFR1, FGFR3 and phosphorylated FOXO3, highlighting their significance in muscle repair and regeneration. These findings provide novel insights into FSN’s potential for counteracting neuropathy-induced muscle damage and improving mitochondrial function, supporting its clinical application. Additionally, FSN’s role in muscle repair suggests a connection between growth factor signaling and nerve regeneration, offering a foundation for future research on muscle-neural recovery mechanisms.